The Correlation of Family Support and Dietary Compliance of The Eldery With Hypertension at Sub-District Health Center Klurahan, Ngronggot District Nganjuk Regency - Henny Purwandari; Erni Tri Indarti; Dimas Kurniansyah (STIKes Patria Husada Blitar, 2021)
Introduction: Current lifestyle triggers an increase in the incidence of hypertension, especially diet. Hypertension sufferers are expexcted to obey the predetermined diet. Family support should be a reinforcing factor that can influence the patient decision to adopt a hypertension diet. The purpose of this study was to determine the correlation of Behavior of Family Support with Dietary Compliance of The Elderly With Hypertension at Sub-District Health Center Klurahan, Ngronggot District, Nganjuk Regency. Methods: Design of the study was a correlation with a cross sectionalÂ approach. This study was conducted on February 23-24 July 2020. The population of this study was all elderly patient with hypertension at Sub-District Health Center Klurahan as many as 38 patients. The sample was 32 respondents taken by purposive sampling technique. The independent variables was The Family Support. The dependent variables was dietary compliance of The Elderly With Hypertension. The Data Collecction used a questionnaire. The data analysis used the Spearman Rank with Î± = (0,05). Results: The results of the study showed almost half of them were 15 respondents (46, 2%) had good family support. Dietary compliance of the elderly most of the wereÂ respondents (51, 3%) Compliance to the hypertension diet. The test results obtained p-value = 0,000 â‰¤ Î± = (0,05) so Ha was accepted with r value was 0, 851 which meant had a very strong level of correlation. Conclusions: Family support is one of the important roles that can help improve care for people with hypertension, support make sufferers more motivated to a compliance hypertension diet.